A systematic review and meta‐analysis: Assessment of hospital walking programs among older patients. Issue 4 (28th November 2022) - Loyd, Christine; Zhang, Yue; Weisberg, Tara; Boyett, James; Huckaby, Elizabeth R.; Grundhoefer, Jeri; Otero, Steve; Roberts, Lisa; Giordano‐Mooga, Samantha; Capo‐Lugo, Carmen; Smith, Catherine H.; Kennedy, Richard E.; et al.
Abstract: Aim: The aim of this study is to assess effect of hospital walking programs on outcomes for older inpatients and to characterize hospital walking dose reported across studies. Design: A systematic review and meta‐analysis examining impact of hospital walking and/or reported walking dose among medical‐surgical inpatients. For inclusion, studies were observational or experimental, published in English, enrolled inpatients aged ≥ 65 yrs hospitalized for medical or surgical reasons. Methods: Searches of PubMed, CINAHL, Embase, Scopus, NICHSR, OneSearch, ClinicalTrials.gov, and PsycINFO were completed in December 2020. Two reviewers screened sources, extracted data, and performed quality bias appraisal. Results: Hospital walking dose was reported in 6 studies and commonly as steps/24 hr. Length of stay (LOS) was a common outcome reported. Difference in combined mean LOS between walking and control groups was −5.89 days. Heterogeneity across studies was considerable ( I 2  = 96%) suggesting poor precision of estimates. Additional, high‐quality trials examining hospital walking and patient outcomes of older patients is needed.